Rugged Large Volume Injection for Sensitive Capillary LC-MS Environmental Monitoring - Roberg-Larsen, Hanne; Abele, Silvija; Demir, Deniz; Dzabijeva, Diana; Amundsen, Sunniva F.; Wilson, Steven R.; Bartkevics, Vadims; Lundanes, Elsa (Frontiers in Chemistry, 2017)
A rugged and high throughput capillary column (cLC) LC-MS switching platform using large volume injection and on-line automatic filtration and filter back-flush (AFFL) solid phase extraction (SPE) for analysis of environmental water samples with minimal sample preparation is presented. Although narrow columns and on-line sample preparation are used in the platform, high ruggedness is achieved e.g. injection of 100 non-filtrated water samples would did not result in a pressure rise/clogging of the SPE/capillary columns (inner diameter 300 µm). In addition, satisfactory retention time stability and chromatographic resolution were also features of the system. The potential of the platform for environmental water samples was demonstrated with various pharmaceutical products, which had detection limits (LOD) in the 0.05 – 12.5 ng/L range. Between-day and within-day repeatability of selected analytes were < 20% RSD.